Employee Performance In Effect Of Organizational Commitment And Work Attitude (Study at the Regional Revenue Service of Palopo City - Wahyudin; M. Risal; Ilham Tahier (Institute of Computer Science (IOCS), 2022)
Employee performance is defined as work performance both in terms of quantity and quality expected of each employee. The better the work atmosphere, the higher the performance, therefore a positive attitude towards work and high organizational commitment will improve the performance of an employee. Based on these problems, this study aims to analyze and empirically test the effect of organizational commitment and work attitude on employee performance at the Regional Revenue Service of Palopo City. The data used in this study is primary data, data collection was carried out using a questionnaire with a scale of 1-5 Liker . The sample in this study were 161 employees of the Regional Revenue Service of Palopo City. Data analysis using SPSS application assistance. The results showed that organizational commitment had no significant effect on employee performance. On the other hand, employee attitudes have a significant influence on employee performance.